2014
DOI: 10.2147/cia.s64758
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 locus and acetylcholinesterase inhibitors in elderly patients with Alzheimer’s disease

Abstract: ObjectiveAcetylcholinesterase inhibitors (AChEIs) may reduce the oxidative stress in brain of Alzheimer’s disease (AD) patients. Forkhead box O1 (FOXO1) protein has been reported as the link between oxidative stress and AD. We evaluated a potential association between FOXO1 gene locus and the response to AChEI treatment in patients with sporadic AD.MethodsIn this prospective study, 109 Caucasian AD patients were treated with standard doses of donepezil, galantamine, or rivastigmine for 6 months. Functional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…FOXO1 gene encodes transcription factor that plays a role in autophagy modulation in neurons ( Xu et al, 2011 ). FOXO1 mutation rs7981045 was associated with response of AD patients to a treatment based on acetylcholinesterase inhibitors ( Paroni et al, 2014 )…”
Section: Biological Mechanisms Linking Autophagy and Admentioning
confidence: 99%
“…FOXO1 gene encodes transcription factor that plays a role in autophagy modulation in neurons ( Xu et al, 2011 ). FOXO1 mutation rs7981045 was associated with response of AD patients to a treatment based on acetylcholinesterase inhibitors ( Paroni et al, 2014 )…”
Section: Biological Mechanisms Linking Autophagy and Admentioning
confidence: 99%
“…FOXO1 is implicated in the cellular response to oxidative stress, and it has been linked to AD through brain insulin resistance. It has been suggested that AChEI may protect cholinergic neurons by enhancing antioxidant activity, and it is possible that the GG genotype of FOXO1 directly contrasts this putative mechanism through increased production of reactive oxygen species (Paroni et al, 2014 ). However, further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the premise above, since younger subjects (with "true" AD pathology) would respond to AChEI in the typical period of months, while older subjects (possibly including LATE patients) would show a slower decline over years, when the effect of AChEI is expected to be clinically negligible (Boccardi et al, 2017). Similar considerations may be made for primary age-related tauopathy (PART), introduced by Crary et al (2014).…”
Section: Demographic Factors: Age Gender Racementioning
confidence: 92%
“…Oxidative stress and AD are linked together by forkhead box O1 (FOXO1) ( Paroni et al, 2014 ; Zhang W. et al, 2020 ). FOXO1 overexpression reduced both tau phosphorylation and Aβ expression ( Zhang W. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%